Costs and Benefits of Labour Mobility between the EU and the Eastern Partnership Partner Countries. Country report. Azerbaijan - Azer Allahveranov; Emin Huseynov (Center for Social and Economic Research (CASE), 2013)
This Report is one of the six studies in the first phase of the EU project on the "Costs and Benefits of Labour Mobility between the EU and the Eastern Partnership Partner Countries". It aims at providing an informed view of the potential for increased migration flows and their consequences as a result of possible changes in the migration policies of the European Union with regard to Azerbaijan. The Report is comprised of 7 Chapters. Chapters 1 and 2 provide a discussion of relevant developments in the economy and labour market in the period since independence, with emphasis on developments over the last ten years or so. Chapter 3 provides a detailed discussion of trends in migration, and discusses the labour migration profile. Chapter 4 analyses remittances and their impact on income, investment and consumption. Chapter 5 provides a discussion of the available evidence on the costs and benefits of labour migration, emphasising the economic, social and demographic costs and consequences. Chapter 6 discusses current migration policies and institutions, while Chapter 7 discusses various factors that may be useful in forecasting key migration trends in the future.
Keywords: D78; F22; F24; I25; J01; J15; J40; J61; J83; 330; Labour Economics; Labour Markets; Labour Mobility; Azerbaijan